(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the current issues of speech technique in the art of baxshi performance and discusses ways of addressing them. It also analyzes the importance of attention to language in the formation of a performer’s speech, as well as the role of speech technique elements. Furthermore, the author presents scholarly views on the influence of bakhshi performance on the formation and development of speech culture in society.